ANÁLISE QUALITATIVA E QUANTITATIVA DA PONTEIRA DA CANA-DE-AÇÚCAR (SACCHARUM OFFICINARUM L.) - Kerpel, Lucas A.; Quadros, Valmir J. d.; Burtti, João V.; Abreu, Fernando B.; Silva, José A. G. d.; Silva, Adair J. d. (Salão do Conhecimento, 2013)
Resumo